Orthopaedic Watercraft Injuries: Characterization of Mechanisms, Fractures, and Complications in 216 Injuries. Issue 4 (April 2018) - Christensen, Joseph; Spence, Sean; Watson, David; Shah, Anjan; Maxson, Benjamin; Infante, Anthony; Sanders, Roy; Mir, Hassan R.
Abstract : Objective: To review the orthopaedic injuries from watercraft treated surgically at our institution and report the mechanisms, fractures, and complications encountered. Design: Retrospective case series. Setting: Level I trauma center. Patients/Participants: There were 216 fractures from watercraft in 146 patients. Average age was 33 years (range 4–78 years), there were 68% males (99/146), and 16% of the injuries occurred in children. Intervention: Operative fracture fixation. Main Outcome Measurements: After IRB approval, data were collected from January 1, 1998, to December 31, 2015, for patients including demographics, watercraft type, mechanism of injury, fracture pattern, infection, organisms, union, and amputation. Descriptive statistics were used. Results: There were 130 closed fractures (60%) and 86 open fractures (40%). There were 146 (67%) lower extremity injuries, 49 (23%) upper extremity injuries, and 21 (10%) pelvic injuries. The overall postoperative infection rate was 9% (20/216) and was commonly polymicrobial in nature. The postoperative infection rate in closed fractures was 4% (5/130) and the postoperative infection rate in open fractures was 17% (15/86). Open fractures also had a high proportion of nonunion (8%) and amputation (16%). Conclusions: This is the largest reported series of orthopaedic injuries from watercraft. These injuries can be devastating in nature and difficult to manage, particularly when they are open (40%). There is a high rate of postoperative infection (17%), nonunion (8%), and amputation (16%) associated with open orthopaedic watercraft fractures. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.